O FAZER JORNALÍSTICO EM TRANSFORMAÇÃO A produção da notícia em mídias independentes digitais - Capobianco, Janaína Cristina Marques (2019)
Journalism is experiencing a moment of structural changes, with profound changes in the dynamics of production, distribution and reception of contents that are changing processes and concepts now consolidated for the theoretical and professional field. This research seeks to understand the processes and productive journalistic routines in digital independent media, with a look at the changes and permanences in relation to traditional journalism, in view of the new technologies and devices of mobile and convergent communication. With a qualitative approach, in a comprehensive perspective of the phenomena, the methodology goes from the survey and bibliographical study to in-depth interviews with founding journalists and/or editors of new independent digital medias expressive in the contemporary Brazilian context. The journalistic dynamics of professionals from seven Brazilian digital independent media are investigated, thus covering a diversity of profiles of these new digital media, from startups to media with a certain engagement and/or political activism. These professional's understanding of traditional media journalism - from many of them came from - is the starting point of the research, which also covers their conceptions of journalism itself and the values that guide them in journalistic action in independent media. Of this way, we intend to analyze a multimedia continuum, from the meta-journalistic practices of professionals to their performance in independent media, in an articulated communicative process and attentive to the new ways of producing and distributing the news. The results point towards a broader and deeper understanding of the new ways of doing journalism, in addition to technical and aesthetic changes, the challenge of permanence and strengthening of ethical references in journalistic practice, in contemporary contexts which increasingly need a quality journalism for citizenship and democracy.